Community-acquired pneumonia briefly about the main. What is important to know to the physician. Based on the materials of the Russian National Congress «Man and Drug» and the III Pulmonology Summit - Yu. V. Evsutina (Лечащий Врач)
Recently more and more cases of viral community-acquired pneumonia have been recorded. Laboratory markers (C-reactive protein, procalcitonin) can help diagnose this disease and determine its prognosis. When choosing an antimicrobial drug, data on antibiotic resistance, the presence of concomitant diseases, previous antibiotic therapy should be taken into consideration. An effective measure for the prevention of community-acquired pneumonia is vaccination against pneumococcus and influenza.